Study of Chemical Composition, Antibacterial and Antioxidant Activities of Rapistrum rugosum L. Essential Oils from Flowers, Leaves, and Stems. Issue 5 (3rd September 2019) - Hichri, Amel Omri; Hichri, Fayçal; Mastouri, Maha; Brahmia, Ameni; Flamini, Guido; Selmi, Boulbaba
Abstract: The chemical composition of the essential oils of three organs (flowers, leaves and stems) from Rapistrum rugosum (L.) All., was studied and screened for their possible antibacterial and antioxidant properties. According to the GC and GC/ MS analysis, 28 (represent 92.5 % of the total oil composition), 23 (93.9 %), and 38 compounds (94.3 %) were identified from flowers, leaves and stems, respectively. The major compound in the leaves essential oil was found to be pentadecanal (55.3 %) followed by hexahydrofarnesylacetone (8.4 %) and tetradecanoic acid (5.7%). While hexahydrofarnesylacetone (17.2 %) followed by 1-pentadecanol (8.3 %), tetradecanoic acid (5.9 %), (E) -β-damascenone (5.7 %) were the major compounds of the flowers oil. Tetradecanoic acid (13.1 %), hexahydrofarnesylacetone (10.1 %), dodecanoic acid (10.0 %), isobornyl acetate (7.6 %), 5-methylthiopentyl isothiocyanate (6.7 %) and (E) -β-ionone (6.2 %) were the main constituents for the stem essential oil. The essential oil of flowers exhibited the higher activity in each antioxidant system (ABTS, DPPH and β-Carotene-linoleic acid methods) with an important value for DPPH assay (PI = 69.88 ± 0.02 %). Furthermore, the isolated oils were tested against five Gram-positive and Gram-negative bacteria. It was found that the essential oil of all organs exhibited interesting antibacterial activities against Gram-positive bacteria, comparable to those of Gentamicin, which was used as positive control.